Effect of lead toxicity on bone calcium content and morphometric parameters - Bhardwaj, Payal; Rai, Durg V. (International Journal of Research in Medical Sciences, 2016)
Background: There is large number of pollutants prevailing in the present environment. Among these, lead (Pb) is of particular interest to us because of its wide distribution in the environment. Large existence of lead (Pb) in number of food items has provoked us to investigate the effects of this metal on bone growth in rats. The present study was designed to evaluate the impact of lead poisoning on bone tissue. Methods: A total of 48 male wistar rats and 30 & 80 days of age were selected for this study. Lead (as lead acetate 250 mg/ml) was provided ad libitum in drinking water for about five weeks to produce subclinical toxicity. Glacial acetic acid was added to the drinking water of lead administered groups at a concentration of 12.5 μl/l to prevent the precipitation of lead acetate. At the termination of treatment period, rats from all four groups were sacrificed by decapitation and their long bones i.e. femur and tibia were excised, cleaned off from soft tissue. Then the bones were preserved in refrigerator (-20oC) and processed for further analysis. Results: Our study revealed that Lead significantly reduced calcium concentration in both femur (p<0.001) and tibia (p<0.001) in lead intoxicated rats. Furthermore, morphometric parameters showed significant reduction in the femoral head width upon lead intoxication. Significant decrease in the ash content of both the bones was observed upon lead intoxication for both the age groups, no significant change observed in the length of the femur as well as tibia of all the treated groups. Conclusions: From this study we can conclude that the lead has induced bone toxicity and has deteriorated the development of bone tissue in the case of growing animals, is the consequence of oxidative stress.